PENGARUH KEPEMIMPINAN KEPALA DESA TERHADAP PENINGKATAN KESADARAN MASYARAKAT DALAM MEMBAYAR PAJAK BUMI DAN BANGUNAN (STUDI KASUS PADA DESA GONDANGLEGI WETAN KAB. MALANG) - Dita Roffal Arisi (Universitas Islam Malang, 2017)
This study aims to determine the influence of Leadership, Communication, Responsibility, Motivation, and Liveliness of village chief to public awareness in paying PBB.By using the sample on the compulsory Land and Building Tax in the village of Gondanglegi Wetan, while research methods including the type of survey research. The results showed that Leadership, Communication, Responsibility, Motivation, and Liveliness of village chief had positive effect topublic awareness in paying Land and Building Tax of 20,7%.